2013
DOI: 10.30955/gnj.000602
|View full text |Cite
|
Sign up to set email alerts
|

Sources and variability of non-methane hydrocarbons in the Eastern Mediterranean

Abstract: The volume mixing ratios of non-methane hydrocarbons including saturated, unsaturated and aromatic ones (C2 to C8 as non methane hydrocarbons, NMHCS) were measured at three distinct sites (natural, rural, urban) in the lower troposphere of the Eastern Mediterranean from February 2006 to March 2007. Average concentrations for most of the NMHC show clear seasonal variations along the year mainly attributed to photochemistry. Significant correlations found among various hydrocarbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Oil pollution is detrimental to the environment and consequently the health of living beings, thus incurring tremendous costs in its cleanup. , Oil spills and industrial oily wastewater discharges have become the major sources of the common aquatic pollution. Studies have reported that, 30 years after an incident occurs, oil residual could still being detected, indicating that the potential indefinite persistency of oil in marine environments and sediments. , Due to the negative effects of oil spill and oily wastewater, treatments or mitigation strategies for oil–water separation have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oil pollution is detrimental to the environment and consequently the health of living beings, thus incurring tremendous costs in its cleanup. , Oil spills and industrial oily wastewater discharges have become the major sources of the common aquatic pollution. Studies have reported that, 30 years after an incident occurs, oil residual could still being detected, indicating that the potential indefinite persistency of oil in marine environments and sediments. , Due to the negative effects of oil spill and oily wastewater, treatments or mitigation strategies for oil–water separation have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used for cleaning up oil or separating oil from oil–water mixture. These methods include combustion, biodegradation, oil skimming, oil adsorption, electric field, magnetic separating, and centrifuging. , Due to its simplicity and ability to fulfill the emergency response of oil spills, absorbing oils from water into porous absorbents, such as low cost sponges, has been most commonly used. ,, One potential issue with the absorption approach is uptake of both oil and water into the absorbent, thus reducing the separation selectivity and efficiency. ,, Furthermore, the difficulty and time-consuming operation in separating oil from the uptake liquid mixture and from the absorbent resulted in burying or burning of the absorbent, leading to additional pollution . As such, to eliminate the separation needs after absorbing liquid, designing absorbents to have specific wettability toward selective absorbing only oil or only water has been investigated extensively in recent years. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations